Indonesian university students’ perceptions of plagiarism: understanding its consequences and the benefits of awareness - Hilyati Fitria Harahap; Arkana Hady; Sholihatul Hamidah Daulay (Erudita: Journal of English Language Teaching, 2025)
Plagiarism remains a persistent challenge in higher education, particularly within Indonesia, where linguistic barriers and academic pressures contribute to its prevalence. Although previous studies have addressed the causes and prevalence of plagiarism, limited attention has been paid to students’ understanding of its academic consequences and the benefits of such awareness. This study investigates Indonesian EFL university students’ perceptions of plagiarism, focusing on their knowledge of its consequences in research writing and the perceived advantages of understanding these repercussions. Adopting a qualitative descriptive-exploratory design with quantitative support, data were collected from twenty students through open- and closed-ended questionnaires. Thematic and descriptive statistical analyses revealed that while students showed general awareness of plagiarism’s academic and legal consequences, gaps remained in their understanding of severe penalties. Moreover, students perceived that awareness of plagiarism consequences helped them avoid academic dishonesty, boosted confidence, promoted responsible behavior, and reduced the temptation to plagiarize. These findings imply the need for more comprehensive, practical academic integrity education to strengthen students’ ethical writing practices and enhance institutional efforts to combat plagiarism.